Multifunctional wiping towel

By adopting a multi-layer structural design in the wipes, combined with bamboo fiber, hemp fiber and PLA composite materials, the shortcomings of existing wipes in water absorption, skin care function and structural stability are solved, and the effects of efficient water absorption, skin care and durability are achieved.

CN119837428APending Publication Date: 2025-04-18HANGZHOU YOUQUAN LIFE TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510235388.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Existing wipes have shortcomings in water absorption, skin care function and structural stability, and it is difficult to meet multiple needs at the same time, especially for sensitive skin or infant skin, which can easily lead to dryness and discomfort.

Method used

The design of multi-layer structure includes a water absorbing layer, a reinforcement layer and a moisturizing layer. The water absorbing layer is made of bamboo fiber, hemp fiber, PLA composite material and SAP powder. The reinforcement layer is made of hemp fiber, PHA, CNF and crosslinking agent. The moisturizing layer is made of hemp pulp viscose fiber, PLA composite material and CNF material. By optimizing materials and processes, it improves water absorption, skin care effect and structural stability.

Benefits of technology

It achieves enhanced water absorption and water storage capacity, efficient skin care functions, optimized functional design, excellent structural stability and durability, and meets environmentally friendly design of degradable materials, meeting the diverse needs of users.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119837428A_ABST
    Figure CN119837428A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of wipes, and discloses a multifunctional wipe, which comprises a water absorption layer, a water storage layer, a water drainage layer, a water drainage layer and a water drainage layer, the moisturizing layer is rich in moisturizing components; the reinforcing layer is located between the water absorption layer and the moisturizing layer, and the purpose of improving the structural strength of the wiping towel is achieved. By optimizing the structure, the materials and the preparation process, the water absorption capacity of the wiping towel is improved, the wiping towel has the skin care and moisturizing effects, high practicability is achieved, the user experience is improved, in addition, due to the combination of the materials, the wiping towel is not prone to being torn or damaged in the using process, the service life is prolonged, durability is improved, and the wiping towel is suitable for popularization and application. The problem that a traditional wet tissue is prone to layering or tearing is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wiping towels, in particular to a multifunctional wiping towel. Background Art

[0002] As people's pace of life accelerates and they pay more attention to personal hygiene, disposable face towels, wet wipes, wet toilet paper, etc. are widely popular because of their convenience and hygiene. These traditional disposable face towels, wet wipes, and wet toilet paper are widely used for cleaning, care and hygiene purposes.

[0003] The wipes in the prior art have some deficiencies in function and structure, and it is difficult to meet multiple needs at the same time. Specifically, although dry wipes have a certain water absorption and can quickly absorb moisture from the skin surface, they lack skin care ingredients and cannot provide moisturizing and care effects for the skin. Especially for sensitive skin or baby skin, it is easy to cause dryness and discomfort after use. On the contrary, wet wipes usually contain skin care ingredients such as glycerin, hyaluronic acid, etc., which can moisturize the skin while cleaning, but because they contain more water, they often cannot quickly and effectively remove excess water from the skin. Instead, they may leave a layer of wetness, affecting the user experience. In addition, the structural design of many wet wipes is not optimized enough, and the fiber layers are not tightly bonded, which leads to easy delamination or tearing during use, reducing durability and cleaning effect. This structural defect not only affects the overall strength and service life of the wipes, but may also cause uneven distribution of skin care ingredients, further affecting the skin care effect.

[0004] Therefore, the wipes in the prior art still need to be improved in terms of water absorption, skin care function and structural stability to better meet the diverse needs of users. Summary of the invention

[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to provide a multifunctional wiping towel.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A multifunctional wipe comprises: a water absorbing layer for absorbing water, the surface of which is provided with a plurality of openings; a moisturizing layer rich in moisturizing ingredients; and a reinforcing layer located between the water absorbing layer and the moisturizing layer for improving the structural strength of the wipe.

[0008] As a preferred technical solution of the present invention, the water-absorbing layer is made of bamboo fiber, hemp fiber, PLA composite material and SAP powder. Taking the total weight of the water-absorbing layer as 100%, the proportions of each material are 40-50%, 25-30%, 20-25% and 5-8% respectively; the reinforcing layer is made of hemp fiber, PHA, CNF and a cross-linking agent containing disulfide bonds. Taking the total weight of the reinforcing layer as 100%, the proportions of each component are 30-35%, 55-60%, 5-8% and 2-3% respectively; the moisturizing layer is made of hemp pulp viscose fiber, PLA composite material and CNF material. Taking the total weight of the moisturizing layer as 100%, the proportions of each component are 60-70%, 20-25% and 5-8% respectively.

[0009] As a preferred technical solution of the present invention, the preparation process of the PLA composite material includes: material preparation: weighing PLA and ATBC, wherein the mass of ATBC accounts for 5-20% of the mass of PLA; drying treatment: placing PLA particles in a vacuum drying oven, drying at 80-100° C. for 4-6 hours, and ensuring that the moisture content is less than 0.05%; mixing and dispersing: adding the dried PLA particles and ATBC into the hopper of a twin-screw extruder, setting the extruder temperature to 150-170° C., and the screw speed to 100-200 rpm, melt blending, and forming a uniform blend; cooling and post-processing: rapidly cooling the extruded blend through a cooling device to solidify it into a shape, and using a pelletizer to cut the cooled blend into uniform small particles, and finally obtaining a PLA composite material.

[0010] As a preferred technical solution of the present invention, bamboo fiber and hemp fiber are pretreated, and the pretreatment includes: degumming treatment: preparing alkaline solution to remove pectin and hemicellulose; enzyme treatment: preparing enzyme solution to perform enzymatic hydrolysis treatment on bamboo fiber and hemp fiber to degrade residual lignin and hemicellulose; surface modification: preparing silane coupling agent solution to enhance the compatibility of bamboo fiber, hemp fiber and polymers such as PLA and SAP.

[0011] As a preferred technical solution of the present invention, the preparation steps of the non-woven fabric used for the water-absorbing layer are as follows: Step 1: Weigh the treated bamboo fiber, hemp fiber, PLA composite material particles and SAP powder in proportion, and put them into a high-speed mixer; Step 2: Use an opener to fully open the mixed material to make the fibers loose and without agglomeration; Step 3: Use a carding machine to comb the opened fibers to arrange them neatly; Step 4: Construct a porous structure, use a high-pressure hydroentanglement process to reinforce the water-absorbing layer material, perform hydroentanglement treatment on the transition area between the surface layer and the bottom layer of the material, gradually reduce the hydroentanglement pressure and increase the nozzle spacing; Step 5: Use a drying box to dry the hydroentangled material to obtain a water-absorbing layer non-woven fabric.

[0012] As a preferred technical solution of the present invention, the preparation steps of the non-woven fabric used for the reinforcing layer are as follows: Step 1: weigh the raw materials used for the reinforcing layer in proportion and put them into a high-speed mixer for mixing; Step 2: put the mixed raw materials into a twin-screw extruder for melt extrusion; Step 3: spray the molten mixture through the nozzle of a two-component melt-blown machine; Step 4: guide the sprayed fibers through the air flow and deposit them on the conveyor belt of the web-forming machine to form a non-woven fabric with a tight structure; Step 5: quickly cool and solidify the web-formed non-woven fabric through a cooling device; Step 6: put the cooled and solidified non-woven fabric into an oven for sufficient cross-linking treatment to finally obtain a reinforcing layer non-woven fabric.

[0013] As a preferred technical solution of the present invention, the preparation steps of the non-woven fabric used for the moisturizing layer are as follows: Step 1: weigh and mix the raw materials used for the moisturizing layer in proportion, and put the mixture into an opening machine; Step 2: cross-lay the opened materials; Step 3: reinforce the opened raw materials using a single-layer spunlace process; Step 4: perform hot air shaping treatment on the spunlace-treated materials to finally obtain the moisturizing layer non-woven fabric.

[0014] As a preferred technical solution of the present invention, the water-absorbing layer, the reinforcing layer and the moisturizing layer non-woven fabric are compounded into a whole, which specifically includes the following steps: hydroentanglement fixation: the water-absorbing layer, the reinforcing layer and the moisturizing layer are placed in sequence, with the water-absorbing layer on the outside, the reinforcing layer in the middle and the moisturizing layer on the inside, to form a stacked composite fiber web, and both sides of the composite fiber web are subjected to low-pressure hydroentanglement treatment; ultrasonic lamination reinforcement: the composite material after hydroentanglement treatment is subjected to ultrasonic lamination treatment, and the welding position is located at the edge area of ​​the composite material, and finally a wipe is obtained.

[0015] As a preferred technical solution of the present invention, the operation steps of adding the moisturizing ingredient to the moisturizing layer include: Step 1: adding the moisturizing ingredient to deionized water, stirring evenly to obtain a mixed liquid; Step 2: laying the wipe flat and fixing it to ensure a flat surface, wherein the moisturizing layer is located at the top; Step 3: using a spraying device, gradually moving the spray gun to cover the mixed liquid into the moisturizing layer; Step 4: lightly drying the wipe to which the moisturizing ingredient is added.

[0016] As a preferred technical solution of the present invention, when the wipe is packaged, both sides of the wipe are folded toward the middle, the moisturizing layer rich in moisturizing ingredients is located inside the entire wipe, and the water-absorbing layer is located outside.

[0017] The present invention has the following beneficial effects:

[0018] 1. Enhanced water absorption and water storage capacity: The water absorption layer proposed in this application has been optimized and improved in terms of materials and preparation process. The material has been degummed, enzyme treated and surface modified to improve water absorption and water storage capacity. This design enables the wipes to quickly absorb a large amount of water and effectively lock in water to avoid leakage, thereby improving the overall water absorption performance;

[0019] 2. Efficient skin care function: The material and preparation process of the moisturizing layer designed in this application can reduce the water absorption of the layer, so that the moisturizing skin care ingredients in the moisturizing layer can be effectively applied to the skin when the user wipes, avoiding the problem that the moisturizing liquid cannot be effectively transferred due to the strong water absorption of traditional wet wipes, and avoiding the waste of moisturizing ingredients;

[0020] 3. Functional optimization: The wipe designed in this application combines the water absorption layer, the reinforcement layer and the moisturizing layer together, which not only ensures the absorption of moisture on the skin, but also plays a role in skin care, has high practicality and improves the user experience;

[0021] 4. Excellent structural stability and durability: The wipes of the present application introduce a reinforcement layer, the hemp fiber provides high strength and wear resistance, PHA as the main matrix material ensures flexibility, CNF enhances the interfacial bonding force, and the cross-linking agent further improves the mechanical strength of the material. The combination of these materials makes the wipes less likely to tear or break during use, prolongs the service life, and improves durability, solving the problem of easy delamination or tearing of traditional wet wipes;

[0022] 5. Environmental friendliness: This application uses a variety of biodegradable materials, which can gradually decompose in the natural environment, reducing pollution to the environment. The design is in line with the concept of sustainable development, reduces the impact of wipes on the environment, and meets environmental protection needs. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a schematic structural diagram of a multifunctional wipe proposed by the present invention;

[0024] Figure 2 It is a schematic diagram of the structure when the wipes are stacked;

[0025] Figure 3 A flow chart for the preparation of wipes;

[0026] Figure 4 Flow chart for hydroentanglement and ultrasonic lamination reinforcement. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0028] Reference Figure 1-4 , a multifunctional wipe comprising:

[0029] The water-absorbing layer is used to absorb water, and a plurality of openings are arranged on its surface; the thickness of the non-woven fabric of the water-absorbing layer is 0.2-0.5 mm;

[0030] The moisturizing layer is rich in moisturizing ingredients and plays a role in skin care. The thickness is 0.3-0.5mm;

[0031] The reinforcing layer is located between the water absorbing layer and the moisturizing layer, and serves to improve the structural strength of the wipes. The thickness is in the range of 0.1-0.3 mm.

[0032] Among them, the water-absorbing layer is made of bamboo fiber, hemp fiber, PLA composite material and SAP (starch-based super absorbent polymer) powder. Calculated based on the total weight of the water-absorbing layer itself as 100%, the proportions of each material are 40-50%, 25-30%, 20-25% and 5-8% respectively. Among them, bamboo fiber provides high water absorption and antibacterial properties, hemp fiber can enhance the overall structural strength, PLA can ensure the bonding strength between the components, and SAP can enhance the water storage capacity and ensure the water absorption performance of the water-absorbing layer.

[0033] Further, the bamboo fiber and the hemp fiber are pretreated, and the pretreatment includes:

[0034] Degumming treatment: Bamboo fiber and hemp fiber contain a lot of lignin, hemicellulose and other impurities, which will affect the water absorption and softness of the fiber. Therefore, degumming treatment is required, including:

[0035] Step 1: using sodium hydroxide (NaOH) solution with a concentration of 5%-10% to obtain alkali solution;

[0036] Step 2: Soak the crushed fiber material in lye for 4-6 hours, keeping the solution temperature at 80-90°C, which helps to accelerate the degumming process. Stir regularly during the process to ensure that the fiber is evenly exposed to the lye.

[0037] Step 3: Rinse the alkali-treated fiber with plenty of clean water until the outflowing water is neutral and the pH value is about 7;

[0038] Step 4: Perform a final rinse with deionized water to remove residual alkali;

[0039] Step 5: In order to further improve the whiteness of the fiber, bleaching treatment is performed, the bleaching agent is hydrogen peroxide (H2O2), the concentration is 3%-5%, the soaking time is 1-2 hours, and the temperature is controlled at 50-60°C;

[0040] Step 6: Rinse thoroughly with clean water.

[0041] Enzyme treatment: In order to further improve the hydrophilicity and water absorption of bamboo fiber and hemp fiber, enzyme treatment method is adopted, including:

[0042] Step 1: Prepare enzyme solution, using cellulase or pectinase at a concentration of 0.5%-1%, and add an appropriate amount of buffer, such as phosphate buffer, with a pH value of about 5-6 to maintain a suitable reaction environment;

[0043] Step 2: Place the cleaned fiber into the enzyme solution, control the temperature at 45-55°C, soak for 4-6 hours, and stir regularly to ensure that the fiber is fully exposed to the enzyme solution.

[0044] Step 3: Stop the enzymatic hydrolysis and heat to 90-100°C for 10-15 minutes to inactivate the enzyme activity;

[0045] Step 4: Rinse again with clean water until the water runs clear.

[0046] Surface modification: In order to improve the compatibility of bamboo fiber and hemp fiber with other materials such as PLA, SAP, etc., surface modification treatment is carried out, including:

[0047] Step 1: Prepare a silane coupling agent solution such as KH-550 with a concentration of 1%-2%;

[0048] Step 2: Soak the treated fiber in the silane coupling agent solution at a temperature of 60-70°C for 1-2 hours, stirring regularly to ensure that the fiber is evenly exposed to the solution;

[0049] Step 3: Drying: Take out the surface-modified fiber and dry it in an oven at a temperature of 60-80°C for about 12-24 hours until the fiber is completely dry.

[0050] After the above-mentioned enzyme treatment, the residual lignin and hemicellulose can be further degraded to make the fiber purer. Secondly, the enzyme treatment can destroy the non-cellulose components in the fiber, increase the softness and hydrophilicity of the fiber, thereby improving the water absorption performance. The enzyme-treated hemp fiber is easier to carry out subsequent processing such as opening and combing, and reduce the entanglement between fibers. The silane coupling agent treatment can form a layer of organic functional groups on the surface of the hemp fiber, enhance its compatibility with polymers such as PLA and SAP, improve the overall performance of the composite material, and at the same time enhance the bonding force between fibers, and improve the mechanical strength and durability of the final product.

[0051] Furthermore, the preparation steps of the water-absorbing layer non-woven fabric are as follows:

[0052] Step 1: Mixing: weigh the treated bamboo fiber, hemp fiber, PLA composite material particles and SAP powder according to the designed proportion, put them into a high-speed mixer, the speed is 300-600rpm, and the mixing time is 20-40min;

[0053] Step 2: Opening: Use an opening machine to fully open the mixed materials to make the fibers loose and free of agglomeration, wherein the air flow velocity is 10-30m / s and the opening roller speed is between 500-1500rpm;

[0054] Step 3: Combing: Use a carding machine to comb the opened fibers to arrange them neatly. The speed of the carding roller is between 800-2000rpm and the carding pressure is between 0.1-0.5MPa.

[0055] Step 4: Construct a porous structure, using an air-laid process or a high-pressure spunlace process. When using the high-pressure spunlace process, for the surface layer, set the high-pressure spunlace pressure to 120-150 bar, the nozzle spacing to 1-2 mm, and the nozzles to be densely arranged to ensure that the fibers are fully entangled and form a fine pore structure. For the bottom layer, set the high-pressure spunlace pressure to 60-80 bar, the nozzle spacing to 5-10 mm, and the nozzles to be sparsely arranged to form a larger pore structure. Perform spunlace treatment in the transition area between the surface layer and the bottom layer, gradually reduce the spunlace pressure and increase the nozzle spacing to form a smooth pore transition, and finally form a high-density microporous structure on the surface layer with a pore size of 1-10 μm, and the pore size gradually increases, and form a macroporous structure with a pore size of 50-100 μm in the bottom layer;

[0056] By controlling the direction of water flow and the distance between nozzles, the fibers are guided to form different arrangements in different areas, thus achieving a gradient pore structure. The surface layer adopts a high-density microporous structure to quickly absorb water; the bottom layer adopts a macroporous structure to store water and enhance air permeability.

[0057] Step 5: Drying: Use a drying box for drying at a temperature of 60-70°C, which can effectively remove moisture without causing significant shrinkage or deformation of the fiber web. The drying time is 10-20 hours.

[0058] The reinforcing layer is made of hemp fiber, PHA (polyhydroxyalkanoate), nanocellulose (CNF) and a cross-linking agent containing disulfide bonds. Taking the total weight of the reinforcing layer as 100%, the proportions of each component are 30-35%, 55-60%, 5-8% and 2-3% respectively. Hemp fiber has high strength and wear resistance. PHA is the main matrix material with good flexibility and fast degradation rate, which can ensure the overall softness of the wipe. CNF can enhance the interface bonding force and improve the tear resistance.

[0059] Cross-linking agents containing disulfide bonds include but are not limited to cystamine, cystine and bisacrylamide. Disulfide bonds (SS bonds) are covalent bonds that can form cross-linked structures between polymer chains, thereby significantly improving the mechanical strength and heat resistance of the material, enhancing the mechanical strength and durability of PHA, and effectively preventing the material from breaking or deforming due to external stress during use, thereby extending the service life of the product.

[0060] Furthermore, the preparation steps of the reinforcement layer non-woven fabric are as follows:

[0061] Step 1: High-speed mixing: put hemp fiber, PHA particles, CNF, and cross-linking agent into a high-speed mixer in sequence, set the speed to 400 rpm, and mix for 20 minutes to ensure uniform mixing;

[0062] Step 2: melt extrusion, put the mixed raw materials into a twin-screw extruder, set the feed zone temperature to 120-130°C, the middle zone temperature to 130-140°C, the die zone temperature to 140-160°C, and the screw speed to 200-300rpm for melt extrusion;

[0063] Step 3: Two-component melt-blowing, the molten mixture is sprayed out through the nozzle of the two-component melt-blowing machine, the temperature is set to 140-160°C, the pressure is 5-10 bar, and the fiber diameter is controlled between 1-10 microns by adjusting the nozzle aperture and air flow speed;

[0064] Step 4: Web formation, the ejected fibers are guided by airflow and evenly deposited on the conveyor belt of the web forming machine, the airflow speed is set to 10-30m / s, the collection distance is 10-30cm, and the conveyor belt speed is 1-3m / min to form a non-woven fabric with a compact structure;

[0065] Step 5: Cooling and curing: The non-woven fabric after being webbed is quickly cooled and cured through a cooling device, and the cold air temperature is set to 20-25°C and the wind speed is 5-10m / s;

[0066] Step 6: Cross-linking treatment: Place the cooled and solidified non-woven fabric in an oven for cross-linking treatment, set the temperature to 120-140°C, and the time to 10-15 minutes to ensure that the cross-linking agent and PHA can be fully cross-linked to form a stable three-dimensional network structure, and finally obtain a reinforced layer non-woven fabric.

[0067] Optionally, the reinforcing layer non-woven fabric is subjected to plasma treatment. Specifically, a radio frequency plasma processor is used, a suitable gas such as CF4 is selected, and the prepared reinforcing layer non-woven fabric is placed in the working chamber of the plasma treatment equipment for plasma treatment, wherein the gas flow rate is 30-40sccm, the power is 200-250W, and the treatment time is 2-3min.

[0068] Among them, the moisturizing layer is made of hemp pulp viscose fiber, PLA composite material and CNF material. Taking the total weight of the moisturizing layer itself as 100%, the proportions of each component are 65-70%, 25-30% and 5-8% respectively.

[0069] Further, the hemp pulp viscose fiber is pretreated, specifically, the hemp pulp fiber is immersed in a silane coupling agent containing a long-chain alkyl group or other hydrophobic groups, such as methyltriethoxysilane, the silane coupling agent solution concentration is 1.5%-2%, the pH is about 5.5, the temperature is 50-60°C, constant temperature stirring is performed for 2-3 hours, and then centrifugal dehydration is performed at a speed of 2500-3500rpm for 3-6 minutes to remove excess solution; hot air drying at 80°C to a moisture content of ≤5%, the fiber contact angle is increased to above 85°, and the moisture absorption rate is ≤6%.

[0070] Furthermore, the preparation steps of the moisturizing layer non-woven fabric are as follows:

[0071] Fiber mixing: pre-treated hemp pulp fiber, PLA composite material and CNF are mixed and put into the opening machine at a speed of 400-600rpm for 15-30min;

[0072] Carded web: cross-laid, weight 50-80gsm, CV ≤ 3%;

[0073] Hydroentanglement reinforcement: single-layer hydroentanglement process, pressure 80-100 bar, pore size uniformly controlled at 10-50μm;

[0074] Hot air setting: The hot air temperature is 70-80℃, the time is 3-6 minutes, and finally a moisturizing layer non-woven fabric is obtained.

[0075] Further, the preparation process of the PLA composite material is:

[0076] Material preparation: Select a suitable type of PLA (such as PLLA, PDLLA, etc.), weigh an appropriate amount of ATBC in proportion, where the mass of ATBC accounts for 5-20% of the mass of PLA;

[0077] Drying treatment: Place the PLA pellets in a vacuum drying oven and dry them at 80-100°C for 4-6 hours to ensure that the moisture content is less than 0.05%. The purpose is to remove moisture from the PLA pellets to prevent bubbles or other defects in subsequent processing;

[0078] Mixing and dispersion: Add the dried PLA particles and ATBC into the hopper of the twin-screw extruder, set the extruder temperature to 150-170°C, the screw speed to 100-200rpm, and perform melt blending to ensure that PLA and ATBC are fully mixed at high temperature to form a uniform blend;

[0079] Cooling and post-processing: The extruded blend is quickly cooled by a cooling device (such as a cold water tank or air cooling device) to solidify it into shape, and a pelletizer is used to cut the cooled blend into uniform small particles for subsequent processes such as web laying and spunlace.

[0080] Furthermore, the water absorbing layer, the reinforcing layer and the moisturizing layer are compounded into a whole, and the specific operation is as follows:

[0081] Hydroentanglement:

[0082] Step 1: Place the water-absorbing layer, the reinforcing layer and the moisturizing layer in sequence, with the water-absorbing layer on the outside, the reinforcing layer in the middle, and the moisturizing layer on the inside, to form a stacked composite fiber web;

[0083] Step 2: Pre-wetting treatment: before hydroentanglement, the composite fiber web is pre-wetted to reduce the impact damage of water flow on the fiber during the hydroentanglement process, wherein the pre-wetting is completed using a low-pressure spray system;

[0084] Step 3: subjecting the composite fiber web to water jet impact, wherein the water jet pressure is 50-60 bar. Using a lower water pressure can reduce the impact force on the fiber, thereby reducing the mixing of the fibers between layers. The nozzle spacing is 1.5-2.5 mm. Increasing the nozzle spacing can reduce the area covered by each nozzle, thereby reducing the degree of entanglement between fibers. The conveyor belt speed is 4-6 m / min. Increasing the conveyor belt speed can shorten the residence time of the fiber web under the high-pressure water flow and reduce the entanglement between fibers. The impact direction is only longitudinal or transverse impact;

[0085] Step 4: Turn the composite fiber web over, and perform hydroentanglement reinforcement on the other side of the composite fiber web according to step 3;

[0086] Step 5: Dehydration treatment: After the spunlace is completed, a vacuum dehydration device is used to remove excess water to ensure that the fiber web is dry and has a certain strength. The vacuum degree is -0.06 to -0.08MPa to ensure that excess water is effectively removed to obtain a preliminarily fixed composite material.

[0087] The hydroentanglement process can cause the fibers between two adjacent layers to be slightly entangled, ensuring connectivity while effectively separating the moisture-retaining layer from the water-absorbing layer.

[0088] Ultrasonic lamination reinforcement:

[0089] Step 1: Preheat the mold, start the ultrasonic welding machine, preheat the mold to the set temperature, the set temperature is 100-150℃, the preheating time is 5-10 minutes, ensure that the mold reaches a uniform temperature to ensure a good welding effect;

[0090] Step 2: Apply pressure, place the cut composite material on the workbench of the ultrasonic welding machine, and ensure that it is accurately positioned. Apply pressure through a pneumatic or hydraulic system to ensure that the fiber mesh is in close contact during the welding process. The pressure is 2-3MPa to avoid excessive compression of the fiber due to excessive pressure.

[0091] Step 3: Ultrasonic welding: Start the ultrasonic generator to generate high-frequency vibration, which is transmitted to the fiber mesh through the welding head to melt the fibers and combine them together. The welding time is 0.5-1.5 seconds, and the vibration frequency is 20-40kHz. The welding position is located at the edge area of ​​the composite material to ensure the strength of the overall structure. Local welding such as spot welding or line welding is performed at the junction of the reinforcement layer and the upper and lower layers to avoid excessive impact on the water absorption layer and the moisture retention layer.

[0092] Step 4: Cooling and shaping. After welding is completed, continue to maintain the pressure for 1-2 seconds to allow the welding area to cool and shape, ensure the structural stability of the fiber web, and finally obtain the composite wipes.

[0093] Furthermore, the moisturizing ingredients in the moisturizing layer include, but are not limited to, glycerin, hyaluronic acid, plant extracts such as aloe vera, green tea, witch hazel, hyaluronic acid, etc.

[0094] Furthermore, the moisturizing component is added to the moisturizing layer of the above-mentioned wipes by spraying, and the specific steps are as follows:

[0095] Step 1: Add the moisturizing ingredients into deionized water and stir evenly to obtain a mixed solution;

[0096] Step 2: lay the above-prepared wipe flat and fix it to ensure that the surface is flat, with the moisturizing layer being on the top;

[0097] Step 3: Use the spraying equipment, keep the distance between the spray gun and the surface of the moisturizing layer at 10-20cm, set the spraying pressure to 0.3-0.5MPa, and move the spray gun gradually to ensure that each part can be evenly covered;

[0098] Step 4: Lightly dry, use a low-temperature air-drying device or dry naturally to remove excess moisture or solvent, but do not dry completely. The purpose is to allow the skin care ingredients to be evenly distributed between the fibers, while avoiding excessive liquid from affecting subsequent use, and finally produce a complete wipe. Specifically, the air-drying temperature of the low-temperature air-drying device is 40-50°C, and the time is 5-10 minutes. Remove excess solvent, and then cool naturally to ensure that the final product maintains a certain humidity so that the skin care ingredients can be effectively transferred to the skin when used.

[0099] It is worth mentioning that when the prepared wipes are packaged, both sides of the wipes are folded toward the middle position, so that the moisturizing layer rich in moisturizing ingredients is located inside the entire wipe, and the water-absorbing layer is located outside. This can effectively retain the moisturizing ingredients, especially when multiple wipes are packaged together, after each wipe is folded, the wipes are stacked and packaged so that the water-absorbing layers of each wipe are in contact. When using, the user can first use the water-absorbing layer of the wipe to wipe and absorb moisture on the skin according to needs, and then turn the wipe over and wipe it again with the moisturizing layer. At this time, the moisturizing ingredients in the moisturizing layer can be applied to the skin to play a skin care role.

[0100] Embodiment 1

[0101] The specific steps for pre-treating bamboo fiber and hemp fiber are as follows:

[0102] Degumming treatment: Use 5% NaOH solution, put the crushed bamboo fiber and hemp fiber into the lye solution, soak for 4 hours, keep the solution temperature at 85℃, stir every 30 minutes, then rinse the fiber with a large amount of clean water until the pH value of the outflowing water is about 7, then use deionized water for the final cleaning, then use 3% H2O2 solution, soak for 1.5 hours at 55℃, and then rinse thoroughly with clean water;

[0103] Enzyme treatment: Use 0.7% cellulase solution, add appropriate amount of phosphate buffer to make the pH value 5.5, put the washed fiber into the enzyme solution, soak it at 50℃ for 5 hours, stir it every 30 minutes, then heat it to 95℃ for 12 minutes to inactivate the enzyme activity, and rinse the fiber with clean water until the water flowing out is clear;

[0104] Surface modification: Use 1.5% KH-550 silane coupling agent solution, soak the treated fiber in the silane coupling agent solution at 65°C for 1.5 hours, stir every 30 minutes, then take out the surface-modified fiber and dry it in an oven at 70°C for 18 hours until the fiber is completely dry.

[0105] Preparation of PLA composite materials, the preparation process is:

[0106] Material preparation: weigh 850 g PLLA and 150 g ATBC;

[0107] Drying treatment: Place the PLLA particles in a vacuum drying oven and dry them at 90°C for 5 hours to ensure that the moisture content is less than 0.05%;

[0108] Mixing and dispersion: PLLA particles and ATBC were added into the hopper of a twin-screw extruder for melt blending. The extruder temperature was 160 °C and the screw speed was 150 rpm.

[0109] Cooling and post-processing: The extruded blend is rapidly cooled through a cold water tank to solidify it into a shape. The temperature of the cold water tank is 20°C, and then pelletized.

[0110] The preparation steps of the water-absorbing layer non-woven fabric are as follows:

[0111] Mixing: Weigh 450g of treated bamboo fiber, 280g of hemp fiber, 230g of PLA composite particles and 40g of SAP powder, put them into a high-speed mixer at a speed of 450rpm and mix for 30min;

[0112] Opening: Use an opener to fully loosen the mixed materials, with an air flow velocity of 20m / s and an opening roller speed of 1000rpm to ensure that the fibers are loose and free of agglomeration;

[0113] Combing: Use a carding machine to comb the opened fibers, with a carding roller speed of 1500rpm and a carding pressure of 0.3MPa to arrange the fibers neatly;

[0114] Constructing porous structure: Using high-pressure spunlace technology, the high-pressure spunlace pressure of the surface layer is 130 bar, the nozzle spacing is 1.5 mm, and the high-pressure spunlace pressure of the bottom layer is 70 bar, and the nozzle spacing is 7 mm. During the transition, the spunlace pressure is gradually reduced and the nozzle spacing is increased to form a smooth pore transition;

[0115] Drying: Use a drying oven, the drying temperature is 65°C, the time is 15 hours, and finally the water-absorbing layer non-woven fabric is obtained.

[0116] The performance of the water-absorbing layer non-woven fabric is tested:

[0117] Among them, the average thickness is 0.44mm (number of measurement points: 5), the water absorption rate is ≥96.4%, the porosity is ≥57.8%, and the tensile strength is ≥18.2N / cm 2 , elongation at break ≥ 25%.

[0118] Embodiment 2

[0119] The preparation steps of the reinforcement layer non-woven fabric are as follows:

[0120] Mixing: Weigh 320 g of hemp fiber, 580 g of PHA granules, 70 g of CNF, and 30 g of cystamine, and put them into a high-speed mixer at a mixer speed of 400 rpm for 20 min;

[0121] Melt extrusion: the mixture was fed into a twin-screw extruder, wherein the temperature of the feed zone of the twin-screw extruder was 125°C, the temperature of the middle zone was 135°C, the temperature of the die zone was 150°C, and the screw speed was 250rpm;

[0122] Two-component melt-blown: The molten mixture is sprayed out through the nozzle of the two-component melt-blown machine, and the fiber diameter is controlled between 1-10 microns. The temperature of the two-component melt-blown machine is 150°C, the pressure is 8 bar, the nozzle aperture is 0.5 mm, and the air flow speed is 20 m / s.

[0123] Web forming: The ejected fibers are guided by airflow and evenly deposited on the conveyor belt of the web forming machine. The airflow speed of the web forming machine is 20m / s, the collection distance is 20cm, and the conveyor belt speed is 2m / min.

[0124] Cooling and curing: The non-woven fabric after being webbed is quickly cooled and cured through a cooling device, with a cold air temperature of 22°C and a wind speed of 7m / s;

[0125] Full cross-linking treatment: The cooled and solidified non-woven fabric is placed in an oven for cross-linking treatment at a temperature of 130°C for 12 minutes, and a reinforced layer non-woven fabric is finally obtained after cooling.

[0126] The performance of the reinforcing layer non-woven fabric is tested:

[0127] The average thickness is 0.23mm (number of measurement points: 5), and the tensile strength is ≥21.7N / cm 2 , elongation at break ≥26.6%.

[0128] Embodiment 3

[0129] The hemp pulp viscose fiber is pretreated by immersing the hemp pulp fiber in a 1.8% methyltriethoxysilane solution with a pH value of about 5.5 and a temperature of 55°C, and stirring at a constant temperature for 2.5 hours; centrifugal dehydration at a speed of 3000 rpm for 5 minutes; hot air drying at 80°C until the moisture content is ≤5%, the fiber contact angle is increased to above 85°, and the moisture absorption rate is ≤6%.

[0130] The PLA composite material used was the PLA composite material prepared in Example 1.

[0131] The preparation steps of the moisturizing layer non-woven fabric are as follows:

[0132] Fiber mixing: 680 g hemp pulp viscose fiber, 270 g PLA composite material, and 50 g CNF were weighed, mixed, and put into the opener at a speed of 500 rpm for 20 min;

[0133] Carding: cross-lapping, weight: 65gsm, CV value (coefficient of variation): ≤3%;

[0134] Hydroentanglement: Single-layer hydroentanglement process, pressure is 90bar;

[0135] Hot air setting: the hot air temperature is 75°C, the time is 5 minutes, and finally a moisturizing layer non-woven fabric is obtained.

[0136] The performance test of the moisturizing layer is as follows:

[0137] The average thickness is 0.46mm (number of measurement points: 5), and the tensile strength is ≥20.2N / cm 2 , elongation at break ≥ 24.9%, moisture absorption ≤ 5.8%.

[0138] Embodiment 4

[0139] The water absorbing layer in Example 1, the reinforcing layer in Example 2, and the moisturizing layer in Example 3 are compounded into a whole, and the specific operation is as follows:

[0140] Hydroentanglement reinforcement: Place the water-absorbing layer, the reinforcing layer and the moisturizing layer in sequence, with the water-absorbing layer on the outside, the reinforcing layer in the middle and the moisturizing layer on the inside, to form a stacked composite fiber web; Use a low-pressure spray system to pre-wet the composite fiber web, with a spray pressure of 2 bar and a time of 1.5 min, and hydroentangle the composite fiber web with a water pressure of 55 bar, a nozzle spacing of 2 mm, a conveyor belt speed of 5 m / min, and an impact direction of only the longitudinal direction; Turn the composite fiber web over, and perform hydroentanglement reinforcement on the other side of the composite fiber web according to the above steps; Use a vacuum dehydration device to remove excess water, with a vacuum degree of -0.07 MPa;

[0141] Ultrasonic lamination reinforcement: start the ultrasonic welding machine, preheat the mold to 125°C, and the preheating time is 7 minutes; apply pressure to the composite fiber web: 2.5MPa, start the ultrasonic generator, welding time: 1 second, vibration frequency: 30kHz, welding position: local spot welding is performed on the edge area of ​​the composite material and the junction between the reinforcement layer and the upper and lower layers; after welding is completed, continue to maintain the pressure for 1.5 seconds to allow the welding area to cool and set, and finally produce a wipe.

[0142] The wipes were tested for performance:

[0143] Average thickness: 1.1mm (number of measurement points: 5), tensile strength ≥ 48.9N / cm 2 , elongation at break ≥34.4%.

[0144] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A multifunctional wipe, characterized in that: include: A water absorbing layer, used for absorbing water, with a plurality of openings on its surface; Moisturizing layer, rich in moisturizing ingredients; The reinforcing layer is located between the water-absorbing layer and the moisturizing layer, and serves to improve the structural strength of the wipes.

2. A multifunctional wipe according to claim 1, characterized in that: The water-absorbing layer is made of bamboo fiber, hemp fiber, PLA composite material and SAP powder. Taking the total weight of the water-absorbing layer as 100%, the proportions of each material are 40-50%, 25-30%, 20-25% and 5-8% respectively. The reinforcing layer is made of hemp fiber, PHA, CNF and a cross-linking agent containing a disulfide bond. Taking the total weight of the reinforcing layer as 100%, the proportions of the various components are 30-35%, 55-60%, 5-8% and 2-3% respectively. The moisturizing layer is made of hemp pulp viscose fiber, PLA composite material and CNF material. Taking the total weight of the moisturizing layer itself as 100%, the proportions of each component are 60-70%, 20-25% and 5-8% respectively.

3. A multifunctional wipe according to claim 2, characterized in that: The preparation process of the PLA composite material includes: Material preparation: weigh PLA and ATBC, where the mass of ATBC accounts for 5-20% of the mass of PLA; Drying treatment: Place the PLA pellets in a vacuum drying oven and dry them at 80-100°C for 4-6 hours to ensure that the moisture content is less than 0.05%; Mixing and dispersing: Add the dried PLA particles and ATBC into the hopper of a twin-screw extruder, set the extruder temperature to 150-170°C, the screw speed to 100-200 rpm, and perform melt blending to form a uniform blend; Cooling and post-processing: The extruded blend is quickly cooled by a cooling device to solidify it into a shape, and a pelletizer is used to cut the cooled blend into uniform small particles to finally obtain a PLA composite material.

4. A multifunctional wipe according to claim 2, characterized in that: The bamboo fiber and the hemp fiber are pretreated, and the pretreatment includes: Degumming treatment: prepare alkali solution to remove pectin and hemicellulose; Enzyme treatment: Prepare enzyme solution to perform enzymatic hydrolysis on bamboo fiber and hemp fiber to degrade residual lignin and hemicellulose; Surface modification: Prepare silane coupling agent solution to enhance the compatibility of bamboo fiber, hemp fiber and polymers such as PLA and SAP.

5. A multifunctional wipe according to claim 4, characterized in that: The preparation steps of the non-woven fabric used for the water absorbing layer are as follows: Step 1: Weigh the treated bamboo fiber, hemp fiber, PLA composite material particles and SAP powder according to the proportion and put them into a high-speed mixer; Step 2: Use an opener to fully open the mixed material to make the fibers loose and free of agglomeration; Step 3: Use a carding machine to comb the loosened fibers to arrange them neatly; Step 4: Construct a porous structure, use high-pressure spunlace technology to reinforce the absorbent layer material, perform spunlace treatment in the transition area between the surface and bottom layers of the material, and gradually reduce the spunlace pressure and increase the nozzle spacing; Step 5: Use a drying box to dry the spunlace treated material to obtain a water-absorbing layer non-woven fabric.

6. A multifunctional wipe according to claim 4, characterized in that: The preparation steps of the non-woven fabric used in the reinforcement layer are as follows: Step 1: Weigh the raw materials for the reinforcing layer in proportion and put them into a high-speed mixer for mixing; Step 2: Put the mixed raw materials into a twin-screw extruder for melt extrusion; Step 3: Spray the molten mixture through the nozzle of a two-component melt-blown machine; Step 4: The ejected fibers are guided by airflow and deposited on the conveyor belt of the web-forming machine to form a non-woven fabric with a compact structure; Step 5: The non-woven fabric after being webbed is quickly cooled and solidified by a cooling device; Step 6: Place the cooled and solidified non-woven fabric in an oven for sufficient cross-linking treatment to finally obtain a reinforcement layer non-woven fabric.

7. A multifunctional wipe according to claim 2, characterized in that: The preparation steps of the non-woven fabric used for the moisturizing layer are as follows: Step 1: weigh and mix the raw materials used for the moisturizing layer according to proportion, and put the mixture into an opener; Step 2: Cross-lay the loosened material; Step 3: Use a single-layer spunlace process to reinforce the loosened raw materials; Step 4: The spunlace treated material is subjected to hot air setting treatment to finally obtain a moisturizing layer nonwoven fabric.

8. A multifunctional wipe according to claim 7, characterized in that: The water absorbing layer, the reinforcing layer and the moisturizing layer non-woven fabric are compounded into a whole, specifically comprising the following steps: Hydroentanglement fixation: Place the water-absorbing layer, the reinforcing layer and the moisturizing layer in sequence, with the water-absorbing layer on the outside, the reinforcing layer in the middle and the moisturizing layer on the inside, to form a stacked composite fiber web, and perform low-pressure hydroentanglement treatment on both sides of the composite fiber web; Ultrasonic lamination reinforcement: The composite material after hydroentanglement is subjected to ultrasonic lamination treatment, and the welding position is located at the edge area of ​​the composite material to finally produce a wipe.

9. A multifunctional wipe according to claim 8, characterized in that: The operation steps of adding the moisturizing component into the moisturizing layer include: Step 1: Add the moisturizing ingredients into deionized water and stir evenly to obtain a mixed solution; Step 2: Lay the wipe flat and secure it to ensure that the surface is flat, with the moisturizing layer on top; Step 3: Use the spraying equipment to gradually move the spray gun to cover the mixed liquid into the moisturizing layer; Step 4: Lightly dry the moisturizing wipes.

10. A multifunctional wipe according to claim 9, characterized in that: When the wipe is packaged, both sides of the wipe are folded toward the middle position, the moisturizing layer rich in moisturizing ingredients is located inside the entire wipe, and the water-absorbing layer is located outside.

Citation Information

Patent Citations

  • Process for producing high soft and high elastic novel spun-laced clothing dressing

    CN101397723A

  • Preparation method of natural plant fiber-rubber composite material

    CN109206760A

  • Soft and hydrolysis-resistant PLA (polylactic acid) fiber and preparation method thereof

    CN110144639A

  • Wet and dry dual-purpose non-woven material as well as preparation method and application thereof

    CN118372527A

  • Composite cleaning towel

    CN201039956Y